2022
DOI: 10.1136/gutjnl-2021-324295
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, histological and molecular profiling of different stages of alcohol-related liver disease

Abstract: ObjectiveAlcohol-related liver disease (ALD) ranges from never-decompensated ALD (ndALD) to the life-threatening decompensated phenotype, known as alcohol-related hepatitis (AH). A multidimensional study of the clinical, histological and molecular features of these subtypes is lacking.DesignTwo large cohorts of patients were recruited in an international, observational multicentre study: a retrospective cohort of patients with ndALD (n=110) and a prospective cohort of patients with AH (n=225). Clinical, analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Whilst patients with never-decompensated ALD had dysregulated expression of genes in involved in the immune response and extracellular matrix deposition, those with AH had more dysregulation in the products of hepatic reprogramming and bile acid metabolism genes. 41 As these unbiased discovery approaches using multiomics data evolve, the potential of novel therapeutic targets remains very promising. In the interim, hypothesis-based targeting of the known pathophysiological mechanisms has formed the current basis of existing and potential therapies for AH.…”
Section: Pathophys Iology Of Alcohol-a Sso Ciated Liver Inj Urymentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst patients with never-decompensated ALD had dysregulated expression of genes in involved in the immune response and extracellular matrix deposition, those with AH had more dysregulation in the products of hepatic reprogramming and bile acid metabolism genes. 41 As these unbiased discovery approaches using multiomics data evolve, the potential of novel therapeutic targets remains very promising. In the interim, hypothesis-based targeting of the known pathophysiological mechanisms has formed the current basis of existing and potential therapies for AH.…”
Section: Pathophys Iology Of Alcohol-a Sso Ciated Liver Inj Urymentioning
confidence: 99%
“…The particular factors influencing this acute worsening to AH in a subset of those with progressive ALD have yet to be described. However, recent studies have explored significant changes in the metabolomic, 37 epigenomic 38,39 and genomic 40,41 profiles of AH patients, indicating the potential of profiling these disease states with multiomics data. Specifically, Ventura‐Cots et al showed that the transcriptome of cohorts with AH, ‘never‐decompensated’ ALD and controls without ALD differed significantly.…”
Section: Pathophysiology Of Alcohol‐associated Liver Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, sAH patients with elevated blood ferritin, an indicator of iron overload and cirrhosis [ 143 ], do not respond well to GC therapy [ 144 ]. A recent histological study of 225 AH patients shows that bridging fibrosis or cirrhosis is present in 81.8% of AH patients [ 145 ]. Thus, as blood biomarkers of good GC responsiveness in sAH, high keratin-18 fragments, low ferritin, and NLR of 5–8 will indicate acute severe, but still controllable, inflammation and apoptosis without prominent fibrosis/cirrhosis and GCR, which is consistent with the known potent anti-inflammatory and anti-apoptotic effects of GC/GR on the liver [ 44 , 56 ].…”
Section: Gc Resistance/non-responsiveness (Gcr) As a Limiting Factor ...mentioning
confidence: 99%
“…Though they are referred to separately, there is substantial histological and diagnostic overlap between AAH and alcohol-related cirrhosis [5,6] meaning that alcohol-related challenges in liver transplantation extend far beyond AAH. Indeed, acute presentations of all severe alcohol-related liver disease (ALD) with short alcohol sobriety represent a confluence of challenges requiring interprofessional experts: severe medical disease, urgent clinical timetables, active SUD, risk of altered mental status, and life-and-death decisions.…”
Section: Liver Transplantation In Short Sobriety Alcohol-related Live...mentioning
confidence: 99%